22 Parental Perceptions and Patterns of Cannabis Use During Pregnancy and Breastfeeding at a Canadian Tertiary Obstetrics Centre. (19th August 2020) - Manning, Sarah; Drover, Anne
Abstract: Background: On October 17th, 2018, recreational cannabis use became legalized in Canada. Tetrahydrocannabinol (THC) is the main psychoactive compound in cannabis. It has the ability to cross the placenta and enter fetal tissues during pregnancy and accumulate in breast milk postpartum. There is limited research on the long-term effects of cannabis use, particularly on the developing brain. Canadian guidelines recommend that women who are thinking about becoming pregnant, are pregnant, or breastfeeding should abstain from using cannabis. Objectives: The objective of this study was to investigate parental perceptions and patterns of cannabis use during the pre- and post-natal periods. Design/Methods: Participants were recruited from the women's health unit at a tertiary care centre; a total of 102 patients or partners of patients who were currently pregnant or less than 6 months post-partum were enrolled in the study. Participants consented to complete an anonymous, online questionnaire including previously validated demographic questions and newly developed questions on cannabis use during pregnancy and breastfeeding. Chi-square tests were used for data analysis. Results: Overall, 5.0% of pregnant women and 6.3% of breastfeeding women used cannabis daily or weekly. Women who did not complete high school were significantly more likely to use cannabis during pregnancy than women who completed higher levels of education (p < 0.001). Additionally, women who smoked cigarettes or vaped tobacco during pregnancy were significantly more likely to use cannabis during pregnancy (p < 0.001; p < 0.001). Among all participants, 22.6% and 30.4% believed there was no harm or were unsure of the harm associated with cannabis use during pregnancy and breastfeeding, respectively. Around half of the women who used cannabis during pregnancy or breastfeeding indicated that knowledge of the possible effects on the fetus or child would decrease their cannabis use. The majority of participants reported obtaining their information on cannabis use during breastfeeding from the internet (34.0%); while only 8.1% reported receiving information from a family doctor, 6.5% from an OBGYN, and 1.6% from a pediatrician. Legalization of cannabis had no reported effect on cannabis use during pregnancy and breastfeeding for the majority of participants. Conclusion: It is clear that parents lack information about the safety of cannabis use during pregnancy and breastfeeding. Perinatal counselling should put an emphasis on educating parents on the risks associated with cannabis use during fetal development. In addition, given the overwhelming benefits of breastfeeding, harm reduction approaches to cannabis use while breastfeeding should be investigated.